Temporal Waste Heat Index (TWHI) for Process Efficiency - Mohammad, Abdul Jabbar; Nageneini, Seshagiri (International Journal of Emerging Research in Engineering and Technology, 2022)
By measuring the hidden "waste heat" of time spent by inefficiencies, delay & also interruptions, the Temporal Waste Heat Index (TWHI) is a novel, quantitative tool meant to evaluate time-output efficiency across more numerous locations. TWHI is a diagnostic tool to find regions where time is consumed without producing quantifiable outcomes in a situation where operational time is sometimes distributed over by more numerous sites & also activities. This metric comes from a basic but powerful idea: more complex processes create temporal waste when operations are postponed or stopped, just as machines spew waste heat during ineffective operation. TWHI seeks to provide more executives with a better view of inefficiencies that could otherwise go unnoticed by tying standard productivity measures with actual time operational responsiveness. Three key domains Time-Based Analysis, which gauges the relationship between time spent & also value generated; Latency Mapping, which identifies delays across process nodes; and Disruption Indexing, which tracks the frequency & degree of their operational interruptions are investigated in our work. To create TWHI as a consistent & more flexible index relevant across many other industries, particularly in manufacturing, logistics & remote digital teams, the study uses a hybrid approach combining data modelling, time-motion analysis & also simulation. Results show that companies using TWHI might find 25–40% of unnecessary time, therefore enabling more strategic process optimization. TWHI provides a framework for more predictive efficiency planning, therefore helping teams to forecast the possible effects of future system modifications or delays on operations. TWHI offers a progressive approach for management as employment is more dispersed and time becomes more limited not just tracking hours but also understanding their relevance. The index opens fresh prospects for real-time dashboards, AI-driven process changes, cross-site coordination strategies meant to save waste and improve major production